Factors affecting on Adherence to the Prescribed Drugs in Diabetic Patients Visiting a Tertiary Care Centre - Thapa, Bijay; Pokharel, Paras Kumar; Poudel, Ishwori Sharma; Sharma, Sanjib Kumar; Shyangwa, Pramod Mohan; Sangraula, Himal; Sharma, Archana (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 11-17 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8799